Effect of potassium sorbate as an interface agent in biodegradable bi-layers polymers (2020)
Studies that are focused on the design and development of biodegradable materials with promising physicochemical properties forindustrial use have been of great importance. In this research, bilayer materials were developed using thermoplastic starch (TPS)monolayers assembled with monolayers sheets of amorphous polylactic acid (PLAa) and polycaprolactone (PCL). Potassiumsorbate was evaluated as an interfacial adhesion material. Structural properties of the laminated materials (FTIR and SEM),behaviour with water (rate of water vapour transmission, solubility in water and moisture content) and biodegradation of thematerials were evaluated. Potassium sorbate was found to act as a promising interface agent by increasing adhesion betweenpolymer layers (SEM). The FTIR showed marked changes in the bands of the hydroxyl and carbonyl groups. Due to PLAaand PCL’s hydrophobic character, all bilayers showed excellent barrier properties against water vapor. Finally, the bilayers thatdegrade the fastest are PCL/TPS. These laminated materials are a great alternative to the decrease in the use of conventionalplastics and are applicable as packaging in the food industry.